REVITALIZING YOUTH MORALITY IN CONTEMPORARY AFRICA: ETHICAL INSIGHTS FROM AFRICAN TRADITIONAL RELIGIONS - Mfugale, Castor (International Journal Multidisciplinary (IJMI), 2026)
Objective: This study investigates the influence of African Traditional Religions on youth moral guidance. Method: It employs a mixed-methods approach, with data collected from 72 youth participants through semi-structured interviews and structured questionnaires. Qualitative data were analyzed using content analysis and hermeneutic perspectives, while quantitative data were transcribed, coded, and analyzed using descriptive statistics. Result: The findings reveal that a significant majority (67%) of respondents acknowledge ATR ethics as a substantial influence on youth moral development. Qualitative insights highlight that initiation rites, such as circumcision for males and female genital circumcision for females, serve as pivotal rites of passage imparting values of bravery, social responsibility, and communal obligations. Despite modern influences and the decline of certain practices like female genital mutilation, the essence of ATR-based moral education remains integral to the Tanzanian community's social fabric. Novelty: The research contributes to the broader discourse on the intersection of indigenous religious practices and moral education, offering insights into the adaptive resilience of ATRs in preserving cultural identity and fostering community development.